2023
DOI: 10.1038/s41598-023-31236-0
|View full text |Cite
|
Sign up to set email alerts
|

A neural network-based PDE solving algorithm with high precision

Abstract: The consumption of solving large-scale linear equations is one of the most critical issues in numerical computation. An innovative method is introduced in this study to solve linear equations based on deep neural networks. To achieve a high accuracy, we employ the residual network architecture and the correction iteration inspired by the classic iteration methods. By solving the one-dimensional Burgers equation and the two-dimensional heat-conduction equation, the precision and effectiveness of the proposed me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In practice, data-driven models are trained on numerical simulation results and approximate a solution to the system of equations. The inference step of the successfully trained model takes a fraction of the computational resources compared to the full mechanistic model ( 63 , 64 ).…”
Section: Facets Of Mechanistic Learningmentioning
confidence: 99%
“…In practice, data-driven models are trained on numerical simulation results and approximate a solution to the system of equations. The inference step of the successfully trained model takes a fraction of the computational resources compared to the full mechanistic model ( 63 , 64 ).…”
Section: Facets Of Mechanistic Learningmentioning
confidence: 99%
“…The use of PINNs is currently being studied as a potential replacement for existing numerical techniques. Due to the recent advent of this type of neural networks, the literature is not yet massive, but reports particularly important pivotal works such as e.g [3,4,5,6,7,8,9,10,11,12,13,14,15,16]. A comprehensive review can be also found in [17].…”
Section: Introductionmentioning
confidence: 99%